QTL-seq analysis identified the genomic regions of plant height and days to heading in high-latitude rice - Wang, Rongsheng; Li, Kun; Zhang, Wei; Liu, Hui; Tao, Yongqing; Liu, Yuming; Ding, Guohua; Yang, Guang; Zhou, Yuanhang; Wang, Jiayou; Wu, Licheng; Liu, Baohai; et al. (Frontiers in Genetics, 2024)
Rice (Oryza sativa L.) is one of the most extensive crops in the world. China's Heilongjiang Province is the northernmost rice growing region in the world. However, rice cultivars suitable to grow well in low-latitude regions may not mature normally due to its distinct climate and short frost-free period. It is necessary to precisely determine the frost-free period for each region to make the best use of the rice growth stage, so as to ensure the maturity and yield of different rice cultivars in Heilongjiang Province. The time span of the heading stage is a key parameter for evaluating the adaptability of a rice cultivar to a specific rice-growing region. Given the above, it is of high importance to study associated genes and sites controlling days to heading and plant height of rice in Heilongjiang Province. Bulked segregant analysis (BSA) combined with high-throughput sequencing can effectively exclude interferences from background genomic differences and suitable for analyzing associated sites of complex agronomic traits in early generations. In this study, an F3 segregating population was obtained by crossing two main cultivars that are grown under different temperature and day-light conditions in Heilongjiang. Two pools of extreme phenotypes were built for days to heading (DH) and plant height (PH) of the population, respectively. For SNP and InDel variants obtained from whole-genome resequencing in the pools, association analysis was performed using the Euclidean distance (ED) algorithm and the SNP/InDel index algorithm, respectively. The intersection of SNP and InDel regions associated with the phenotypes was taken to obtain the final associated sitesAfter excluding interferences from the cloned genes on chromosomes 2 and 7, a total length of 6.34 Mb on chromosomes 1, 3, 10 and 3.16Mb on chromosomes 1,10 were left associated with PH and DH, respectively. Then we performed a gene annotation analysis for candidate genes in the remaining regions using multiple genome annotation databases. Our research provides basic data for subsequent gene mapping and cloning. By mining more genetic loci associated with days to heading and plant height of rice, we may provide abundant genetic resources for refined molecular breeding in Heilongjiang province.